Wildfire under a changing climate in the Bolivian Chiquitania: a social-ecological systems analysis - Devisscher, T (2015)
With the same force that human activities accelerate and amplify change in the biosphere, human agency can play a critical role in influencing future trajectories. However, managing increasingly complex problems is becoming ever more challenging. Among other things, it requires a systemic thinking about the future to anticipate how intertwined drivers may respond to rapid change. This thesis addresses such challenge in the context of contemporary wildfires, which are becoming increasingly complex to manage and a growing global concern. The study adopted a novel approach (Chapter 3) to study wildfire as a complex social-ecological system. The overarching aim is to generate insights into wildfire causes, effects and feedbacks to anticipate future wildfire risk and inform management strategies that can prevent potential impacts. I combine different disciplinary lenses, multiple spatial scales of analysis and participatory methods to analyse wildfire dynamics in the Chiquitania region, located in the Department of Santa Cruz, Bolivia, at the southern edge of Amazonia. This region has a unique tropical dry forest that is susceptible to changes in climate and fire regimes, and a rapidly expanding agricultural frontier. During the recent 2010 drought, large wildfires affected this region intensifying public concern about potential ‘mega-fires’, particularly given predictions of more extreme seasonality in the future. The first research paper of this thesis (Chapter 4) evaluates the effects of wildfire recurrence on the forests of the Chiquitania using ecological surveys. In addition to significant biomass loss, the observed patterns in species abundance and dominance suggest that the forests respond to recurrent fires through a shift in tree species composition, with fire-tolerant species becoming more dominant. The second research paper (Chapter 5) analyses future wildfire risk in the Chiquitania region using fuzzy cognitive mapping. This conceptual modelling approach engaged different actor groups in the region to integrate their perspectives of the regional wildfire dynamics. Semi-structured interviews informed the scenario assumptions which considered failure to respond in time to wildfire risk, as well as implementation of alternative management strategies. Unexpectedly, the fire management strategy showed less trade-offs between wildfire risk reduction and production compared to the fire suppression strategy. The high vulnerability of the agricultural production to wildfire risk has implications for local communities that largely depend on agriculture for subsistence if future climatic conditions become drier. The third research chapter (Chapter 6) uses interviews and focus group discussions to analyse how different forms of knowledge and perceptions of fire relate to prevalent wildfire risk strategies in the Chiquitania. The analysis reveals that strategies are in tension between two conflicting narratives and understandings of fire. On this basis, a deliberation process is proposed with the potential to integrate opposing views into more inclusive and collective solutions to manage wildfire risk within a reflexive governance framework. The fourth research paper (Chapter 7) complements the above ground-based studies with a regional assessment of wildfire risk based on remotely sensed land cover, anthropogenic and climatic data. Maximum entropy was used as a probabilistic modelling approach to simulate future wildfire risk scenarios driven by different development trajectories, and assuming changing climatic conditions. Important determinants of wildfire risk were climate, road development, deforestation and density of human settlements. Positive feedbacks between rapid frontier expansion and drought conditions almost doubled potential biomass loss compared to estimates in the 2010 drought. Land used for agriculture and cattle ranching showed particularly high levels of wildfire risk, with serious implications for the subsistence and economy in the Chiquitania if the agricultural frontier is expanded at an accelerated rate. The combination of new findings and modelling tools developed in this thesis are relevant to inform wildfire risk management decisions in the Chiquitania. The timing is fitting as the regional government of Santa Cruz is developing a ten-year programme to address increased wildfire risk at the time of thesis submission, and the recently launched Regional Fire Platform promotes dialogue about possible solutions. More broadly, the approach to study wildfire as a social-ecological system has proven extremely useful to generate insights into different facets of a complex problem that is becoming a major concern in most of Amazonia and globally. This thesis generates important theoretical and practical contributions to the study of social-ecological systems, and provides a concrete example of how increasingly complex problems can be anticipated and managed under climate change and rapidly changing conditions with a more integrated and socially inclusive approach that can inform adaptation decisions for more sustainable futures.